PENERAPAN MODEL PROJECT BASED LEARNING (PjBL) DENGAN MEDIA DIGITAL PADA MATERI PEDOMAN NEGARAKU DI KELAS VIII SMP NEGERI 3 MUARA KOMAM - Abdul Haris (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the implementation of Project Based Learning (PjBL) using digital media on the Pedoman Negaraku (Guidelines of My Country) material and its impact on students’ understanding, skills, and motivation in Grade VIII at SMP Negeri 3 Muara Komam. This classroom action research was conducted in two cycles, involving all students of Grade VIII as research subjects. Data were collected through achievement tests, observation of students’ project skills, participation sheets, and teacher observation. The results indicate that the implementation of PjBL using digital media effectively improves the quality of learning. Student understanding increased, with 85% of students achieving a score ≥75, compared to 60% before the intervention. Students also demonstrated improved skills in creating and presenting digital media projects, with all groups successfully completing their projects. Participation and motivation rose to 90%, and the teacher effectively facilitated the learning process by providing constructive feedback. Challenges, such as limited access to digital devices, were overcome through group collaboration and peer guidance. In conclusion, PjBL with digital media is effective in teaching the Pedoman Negaraku material , enhancing students’ understanding, skills, participation, and motivation, as well as fostering their awareness in applying national values in real life. Keywords: Project Based Learning, Digital Media, Pedoman Negaraku, Student Understanding, Student Skills, Learning Motivation